2010
DOI: 10.1111/j.1471-0528.2010.02751.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal steroids and neonatal outcome after chorioamnionitis: a meta‐analysis

Abstract: Background There is debate concerning the safety and efficacy of antenatal steroids in preterm labour with suspected intrauterine infection (chorioamnionitis).Objectives We performed a systematic literature review and metaanalysis aimed at evaluating the efficacy and safety of antenatal steroids in clinical and histological chorioamnionitis.Search strategy MEDLINE, EMBASE, BioMed Central and the Cochrane databases were searched using the terms 'chorioamnionitis OR intrauterine infection' and '*steroids OR *cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 34 publications
5
58
0
6
Order By: Relevance
“…This finding may be in accordance with the results from a recent meta-analysis showing that, in histological or clinical chorioamnionitis, antenatal steroids were not clearly associated with a reduced incidence of BPD (30). However, this might be related to the timing of the experimental interventions in our study, and further study about different timing of betamethasone treatment would be needed to clarify this.…”
Section: Chorioamnionitis and Steroid For Bpdsupporting
confidence: 82%
“…This finding may be in accordance with the results from a recent meta-analysis showing that, in histological or clinical chorioamnionitis, antenatal steroids were not clearly associated with a reduced incidence of BPD (30). However, this might be related to the timing of the experimental interventions in our study, and further study about different timing of betamethasone treatment would be needed to clarify this.…”
Section: Chorioamnionitis and Steroid For Bpdsupporting
confidence: 82%
“…Been et al [21] recently conducted a meta-analysis of observational studies on this matter and our study adds value to previous studies. The use of antenatal steroids improved outcome of infants and we observed no harmful effects; this is in line with Been et al [21] In addition, Lahra et al [1] recently showed that chorioamnionitis was associated with a decreased incidence of RDS but not BPD.…”
Section: Discussionsupporting
confidence: 70%
“…A recent meta-analysis by Been and colleagues also concluded that antenatal steroids improved neonatal outcomes after preterm birth associated with chorioamnionitis (4). Surprisingly, the antagonistic combination of inflammation and anti-inflammatory glucocorticoids caused more lung maturation than either stimulus alone.…”
Section: Discussionmentioning
confidence: 97%